Penggunaan Alat Peraga Fosil dalam Pembelajaran SKI - Ilman Zikrah; Melina Dwi Putri; Tiwi Tamara; Aulia Umami (JPT : Jurnal Pendidikan Tematik, 2025)
This research is based on an interview with Mrs. Mutmainah, S.Pd., a teacher at SMA IT IQRA Bengkulu City, to evaluate the implementation of the Merdeka Curriculum at the school. The results of the interview show that the high school has implemented the Merdeka Curriculum for 2 years, but the class XII teacher has not used the curriculum because of national exam preparations. The learning method used is not much different from the 2013 Curriculum, with an emphasis on discussions and student projects. The learning media used include PowerPoint presentations, learning videos, and teaching aids such as pictures of fossils, the Koran, maps, and globes. The obstacles faced are limited teaching aids and learning media. However, implementing an independent curriculum provides benefits in terms of ease of delivery of material and active involvement of students in learning.Props